Delivering the Same Intervention to Hispanic/Latinos With Pre-diabetes and Diabetes. Early Evidence of Success in a Longitudinal Mixed Method Study. (1st November 2021) - Joachim-Célestin, Maud; Gamboa-Maldonado, Thelma; Dos Santos, Hildemar; Montgomery, Susanne B
Background: Despite nationwide efforts to address the diabetes epidemic and reduce prevalence disparities, higher rates persist among the poor, especially those with limited literacy. Currently, individuals with abnormal glycemia who have pre-diabetes and diabetes qualify for different programs. However, evidence suggests that, for low-income Hispanic/Latinos, offering a single intervention to all those with abnormal glycemia may provide a more culturally acceptable and effective approach. Our objective was to explore the feasibility of such an intervention led by community health workers (CHWs) among low-income Hispanic/Latinos with diabetes and at risk for diabetes. Methods: Using a quasi-experimental mixed method design, we assessed weight, glycosylated hemoglobin, diabetes knowledge, and behavior changes of Hispanic/Latinos participants with pre-diabetes and diabetes living in Southern California. Biometric measurements, blood tests, and surveys were collected at baseline and 3 months post-intervention. Interviews and focus group discussions provided qualitative data. Results: Although the program was less costly, results exceeded those reported for low-income H/L attending the National Diabetes Prevention Program and did not differ between pre-diabetes and diabetes groups. Instead, including individuals at different stages of the dysglycemic spectrum seemed to have enhanced the intervention. Physician referral and attendance of family/friends were associated with better outcomes. Conclusion: Our findings indicate that a joint prevention/self-management intervention led by CHWs for low-income Hispanic/Latinos with diabetes and with pre-diabetes is feasible and cost-effective, providing results that could help reduce the success gap. Incorporating suggestions and replicating this study on a larger scale could help determine whether or not results are reproducible.